Development of olanzapine solid dispersion by spray drying technique using screening design for solubility enhancement - Leena Patil; Umakant Verma; Rahul Rajput; Pritam Patil; Anniruddha Chaterjee; Jitendra B. Naik (International Association of Physical Chemists (IAPC), 2023)
Introduction: Olanzapine (OLZ) is a psychotropic class drug commonly used to treat schizophrenia, bipolar disorder, and acute manic episodes. It has less water solubility, resulting in a slow dissolution rate and oral bioavailability. Therefore, the development in oral dosage forms is required to enhance the drug solubility. Method: The solid dispersion of olanzapine is prepared by spray drying technique. The solution of polyvinylpyrrolidone K-30 (PVP K-30), mono amino glycyrrhizinate pentahydrate (GLY), OLZ and silicon dioxide were dissolved in distilled water and ethanol and spray dried to get the solid dispersion. Solid dispersion was characterized for surface morphology, solubility, encapsulation efficiency (EE), X-ray diffraction (X-RD), Differential Scanning Calorimeter (DSC) and drug-polymer interaction by Fourier transforms infrared spectroscopy. Results: The amorphous nature of the drug's incorporation in solid dispersion was confirmed by X-RD analysis. Prepared solid dispersion showed higher solubility, 11.51 mg, than pure OLZ (0.983 mg ml-1), while the range of EE was found to be between 64 to 90 %. Conclusions: The solubility and dissolution rate of the OLZ can effectively increase by spray-dried solid dispersion. Plackett-Burman screening design plays a vital role in understanding the effect of independent variables on EE and solubility.